2009
DOI: 10.1016/s0210-4806(09)74112-9
|View full text |Cite
|
Sign up to set email alerts
|

Dolor durante biopsia de próstata guiada por ultrasonografía transrectal: Comparación del uso o no de Xilocaína gel como anestésico local

Abstract: The use of lidocaine gel intrarectal 2% before a prostate biopsy guided by ultrasound did not diminish the sensation of pain from the procedure in our patients, which was increased by the use of sterilized needles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Topical intrarectal application of anesthetic gels (e.g., 2% lidocaine) has been traditionally considered to relieve anal discomfort, but a recent meta-analysis of randomized trials [8] and two subsequent trials [9,10] indicated a lack of an analgesic effect. The present data are in line with these observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Topical intrarectal application of anesthetic gels (e.g., 2% lidocaine) has been traditionally considered to relieve anal discomfort, but a recent meta-analysis of randomized trials [8] and two subsequent trials [9,10] indicated a lack of an analgesic effect. The present data are in line with these observations.…”
Section: Discussionmentioning
confidence: 99%
“…In the five trials embraced by the recent meta-analysis [8] and two subsequent trials [9,10], pain scores on a 10-point visual analogue scale (VAS) in patients undergoing prostate biopsy with or without intrarectal anesthetic gel averaged between 3 and 5.6 with standard deviations (SDs) between 1.5 and 2.7. In an analysis of variance with 3 treatment groups, assuming a mean VAS score of 5 under the null hypothesis and an SD of 2.5, a total of 126 patients (42 per group) would provide 81% power at the overall 0.05 alpha level to detect a mean difference of 1.5 VAS score points between any two treatments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation